Pengembangan Media Pembelajaran Berbasis Android pada Mata Pelajaran Gambar Teknik - Alfian Rifky Zaelani; Khoirul Huda; Kriswanto Kriswanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to develop Android-based learning media for the Technical Drawing subject for grade X students of Machining Engineering at SMK Negeri Jawa Tengah, Semarang. The main focus of this media development is on the material of pictorial and orthogonal projections which have often been a problem for students, because they are abstract and require high visualization skills. This study uses the Research and Development (R&D) method with a 4D model approach (Define, Design, Develop, Disseminate), but is limited to the Develop stage. The media was designed using iSpring Suite software which was then converted into an Android application format via Web2Apk Builder. Validation was carried out by material experts and media experts, as well as practicality tests by students as users. The validation results showed that this learning media was in the "very feasible" category, with an average percentage of 87.5% from material experts, and 84.5% from media experts. The practicality test by 24 students showed a score of 88% which indicates that this media is very practical to use in the learning process. These results indicate that the developed media is classified as very feasible and practical to use in learning activities. This media has the potential to support independent, flexible, and interactive learning for vocational high school students and is an innovative alternative for implementing mobile technology in learning.